Evaluation of the Implementation of Enterprise Resource Planning on Inventory Recording at PT Varia Usaha Beton - Febrilia Yudhistira; Vicky Vendy (GoodWill, 2026)
This study aims to implement an Enterprise Resource Planning (ERP) system for recording raw material inventory at PT Varia Usaha Beton (PT VUB). This company operates in the construction sector and requires an information system that is able to record stock accurately and in real time to help smooth the production process. The research method used is a qualitative approach with a case study method. Data were collected through in-depth interviews with three informants from the procurement and warehouse divisions, as well as direct observation and internal documentation. The results of the study indicate that the implementation of Sunfish ERP improves the efficiency of inventory recording, reduces human error, and allows real-time data integration between departments. However, there are several obstacles such as slow network connections, lack of user discipline, and less than optimal integration of ERP with external systems. The implications of this study indicate that the implementation of ERP can improve operational efficiency and decision making at PT VUB, but requires adequate infrastructure support and HR training. These findings are expected to be the basis for companies in planning policies to improve digital infrastructure, strengthen information system governance, and develop human resources to optimize the benefits of the ERP system as a whole. Keywords (4-5): Enterprise Resource Planning, Inventory, Concrete Business Varieties, Information Systems, Real-Time